Environmental history in the making. Volume I, - Vaz, Estelita; Melo, Cristina Joanaz de; Pinto, Lígia M. Costa (Environmental history series, 2016)
This book is the product of the 2nd World Conference on Environmental History, held in Guimarães, Portugal, in 2014. It gathers works by authors from the five continents, addressing concerns raised by past events so as to provide information to help manage the present and the future. It reveals how our cultural background and examples of past territorial intervention can help to combat political and cultural limitations through the common language of environmental benefits without disguising harmful past human interventions. Considering that political ideologies such as socialism and capitalism, as well as religion, fail to offer global paradigms for common ground, an environmentally positive discourse instead of an ecological determinism might serve as an umbrella common language to overcome blocking factors, real or invented, and avoid repeating ecological loss. Therefore, agency, environmental speech and historical research are urgently needed in order to sustain environmental paradigms and overcome political, cultural an economic interests in the public arena. This book intertwines reflections on our bonds with landscapes, processes of natural and scientific transfer across the globe, the changing of ecosystems, the way in which scientific knowledge has historically both accelerated destruction and allowed a better distribution of vital resources or as it, in today's world, can offer alternatives that avoid harming those same vital natural resources: water, soil and air. In addition, it shows the relevance of cultural factors both in the taming of nature in favor of human comfort and in the role of the environment matters in the forging of cultural identities, which cannot be detached from technical intervention in the world. In short, the book firstly studies the past, approaching it as a data set of how the environment has shaped culture, secondly seeks to understand the present, and thirdly assesses future perspectives: what to keep, what to change, and what to dream anew, considering that conventional solutions have not sufficed to protect life on our planet.- Resumé vydavatel